The Influence of Halogenated Hypercarbon on Crystal Packing in the Series of 1-Ph-2-X-1,2-dicarba-closo-dodecaboranes (X = F, Cl, Br, I) - Havránek, Miroslav; Samsonov, Maksim A; Holub, Josef; Růžičková, Zdeňka; Drož, Ladislav; Růžička, Aleš; Fanfrlík, Jindřich; Hnyk, Drahomír (Molecules (Basel, Switzerland), 2020)
Although 1-Ph-2-X-closo-1,2-C2B10H10 (X = F, Cl, Br, I) derivatives had been computed to have positive values of the heat of formation, it was possible to prepare them. The corresponding solid-state structures were computationally analyzed. Electrostatic potential computations indicated the presence of highly positive σ-holes in the case of heavy halogens. Surprisingly, the halogen•••π interaction formed by the Br atom was found to be more favorable than that of I.
Keywords: Halogenation; Boron Compounds; Chemistry Techniques, Synthetic; halogen bond; icosahedral boron cluster; Models, Molecular; sloučeniny boru; uhlík; Carbon; halogeny; molekulární modely; Molecular Conformation; halogenace; sigma hole; techniky syntetické chemie; Halogens; molekulární konformace